The national minimum wage in the United Kingdom - Dan Finn (Institut Arbeit und Technik (IAT), 2005)
This study assesses the context and development of the British NMW and the evidence of its impact. The study outlines the earlier system of Wages Councils, abolished in 1993 as part of the British Conservative Government's policy that, from the early 1980s, had deregulated much of the British labour market. It explains how the campaign for a National Minimum Wage developed and attracted support from the trade union movement and Labour Party. It details the debate that took place in Britain about the impact of a minimum wage and the arguments for and against its implementation. It then describes the NMW legislation that was introduced in 1998 and the role the minimum wage plays in the New Labour Government's "make work pay" strategy. It reviews the reports produced by the independent Low Pay Commission that makes recommendations to Government about the rate and coverage of the minimum wage in light of prevailing economic circumstances and the representations of interested groups. This study also outlines the impact of the NMW on earnings, wage differentials, employment levels and poverty. It further explains how the NMW is enforced and considers related issues concerning the position of low paid workers earning less than the minimum wage. Finally it explains about a continuing debate on the rate at which the NMW should be set and enforced. – – Diese Studie bewertet den Hintergrund und die Entwicklung des gesetzlichen Mindestlohns in Großbritannien und die Belege für seine Wirkungen. Das vorausgegangene System der Entlohnungsbeiräte, 1993 im Rahmen der Deregulierungspolitik der konservativen Regierung abgeschafft, wird kurz skizziert. Es wird dann erklärt, wie sich die Bewegung für einen gesetzlichen Mindestlohn entwickelte und Unterstützung bei den Gewerkschaften und der Labour Party fand. Die Debatten über die zu erwartenden Wirkungen eines Mindestlohns und das Für und Wider seiner Einführungen werden analysiert. Die Studie beschreibt dann die 1998 eingeführte Gesetzgebung zum Mindestlohn und ihren Stellenwert in der Strategie der Regierung von "New Labour" zur Verbesserung der Arbeitsanreize. Sie fasst die Berichte der unabhängigen Niedriglohn- Kommission zusammen, die in Ansehung der wirtschaftlichen Lage und nach Beratung mit den betroffenen gesellschaftlichen Gruppen Empfehlungen an die Regierung über die Höhe und den Geltungsbereich des Mindestlohns erarbeitet. Die Studie fasst auch die verfügbaren Daten zum Einfluss der Mindestlohngesetzgebung auf Verdienste, Lohnunterschiede, Beschäftigungsniveaus und Armut zusammen. Sie erklärt außerdem, wie der Mindestlohn durchgesetzt wird, und geht auf verwandte Probleme bezüglich der Position von Geringverdienenden ein, deren Lohn geringer ist als der Mindestlohn. Schließlich erläutert sie die aktuelle Debatte über die künftige Höhe und Durchsetzung des Mindestlohns.
Keywords: 330